(untitled) - Rule, David (Burlington, MA., 2007)
This book will detail the default and custom installation of VMware's ESX server as well as basic and advanced virtual machine configurations. It will then walk the reader through post installation configurations including installation and configuration of VirtualCenter. From here, readers will learn to efficiently create and deploy virtual machine templates. Best practices for securing and backing up your virtual environment are also provided. The book concludes with a series of handy, time-saving command and configuration for: bash shell keystrokes, Linux commands, configuration files, common/proc files, VMware ESX commands, and troubleshooting.
Keywords: Operating systems (Computers),Virtual computer systems,Hệ thống điều hành (Máy tính),Hệ thống máy tính ảo